(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The likelihood that certain scourge could alter or shatter educational processes and subsequently impede educational advancement necessitated an investigation on school dropout and educational development in Orashi region, Rivers State. The study adopted the descriptive survey design. The population of the study comprised of all the 1150 teachers in the 68 junior secondary schools in the study area. A multistage sampling technique was used to select 300 junior secondary school teachers and a 30 item structured instrument, validated by two experts was used for the study with a title “School Dropout”. The obtained reliability coefficient of 0.762 justified its use to obtain data that were analyzed using mean and standard deviation. The study revealed that: absenteeism, truancy, non-participation in class/school work, inferiority complex or shyness, etc. were signs that culminate to high school dropout rate. This could be reduced through teacher-induced interventions like: providing emotional support for students who are facing some challenges, adopting waiving disciplinary actions incurred by students, etc. The study recommended among others that: teachers should be responsive and quick to identify and remediate issues like absenteeism, non-participation in class/school work, truancy, inferiority complex, etc. that could disillusion students and culminate to their dropping out of school. Alongside, Government should adopt inventions like emotionally supporting challenged students, etc. in order to stimulate their interest and facilitate the reentry into the school.